Exploring students’ lived experience in online learning during Covid-19 pandemic through a phenomenological hermeneutic perspective - Wiwiek Afifah; Soeharto Soeharto; Lucia H. Winingsih; Budi Kadaryanto; Sabar Budi Raharjo; Fitria Arifiyanti; Zsolt Lavicza (International Journal of Educational Research Open, 2025)
The exploration of students’ lived experiences in online learning during the Covid-19 pandemic is crucial as it offers values that can elicit a sense of better understanding of the world or situation of how Indonesian EFL students experienced their online learning during the pandemic. Many studies on how students learn during the pandemic have been undertaken. However, examining EFL students’ lived experiences in university has not been found in the literature. For the reasons, this study aims to investigate the fundamental aspects of lived experience, how students experienced and responded to online learning, and how the experience shaped their understanding of the world. To know the three points, hermeneutic phenomenology under qualitative research was applied with one hundred and three students’ writings which were collected. Out of the number of participants, fifty-one writings were selected and considered to represent EFL students’ lived experiences. The selected writings then were analysed by using van Manen's method consisting of six steps. The findings revealed that in online learning, the fundamental aspects of students’ lived experience were language acquisition, language learning, interaction, presence, emotional connection, engagement, and memory. To pertain the success of EFL online learning, most of the students’ writing showed pessimist to master and achieve the learning targets as the real interaction was very minimum. Lastly, students' experience greatly influenced by the way they perceived the teaching material being taught in online class. EL students’ perceptions and interpretations of the experiences impacted on their attitudes, values, and beliefs. Their decisions and actions were also influenced by their lived experience.